Identifikasi secara Kualitatif dan Kuantitatif Kandungan Siklamat serta Sakarin pada Minuman “Bubble Tea (Boba)” Komersil - Uswah Choiriyatun Nisa; Amalia Wahyuningtyas; Dina Fithriyani; Zada Agna Talitha (Jurnal Teknologi dan Mutu Pangan, 2024)
Boba drink (bubble tea) is one of the most popular drinks among young people today. This drink has a good taste, but can cause health problems if consumed excessively. The use of synthetic sweeteners in beverage additives is also often used by the food and beverage industry, including cyclamate and saccharin. Thus, it is necessary to identify the sweetener content used in boba drinks. This study aims to identify and measure the levels of artificial sweeteners (Saccharin and Cyclamate) in boba drinks in Bandar Lampung. The research method used is descriptive method using purposive sampling technique. The samples tested were drinks and boba sold at shopping places and cafes in the city of Bandar Lampung. The results showed that there was cyclamate content in the boba drink samples tested based on qualitative tests characterized by the formation of white precipitate, there were five positive samples of cyclamate that exceeded the SNI 01-6993-2004 limit with levels varying from 1510.35 to 2520.89. The highest cyclamate level is owned by the Boba D beverage sample. The saccharin qualitative test showed negative results, indicated by no green color change. This study makes an important contribution in raising consumer awareness of additives in beverages.